2014
DOI: 10.1002/prp2.70
|View full text |Cite|
|
Sign up to set email alerts
|

Isobenzofuranone derivatives exhibit antileishmanial effect by inhibiting type II DNA topoisomerase and inducing host response

Abstract: Leishmania, a protozoan parasite, causes a wide range of human diseases ranging from the localized self-healing cutaneous lesions to fatal visceral leishmaniasis. Toxicity of traditional first line drugs and emergence of drug-resistant strains have worsened the situation. DNA topoisomerase II in kinetoplastid protozoan parasites are of immense interest as drug target because they take part in replication of unusual kinetoplast DNA network. In this study, we have taken target-based therapeutic approaches to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
0
12
1
Order By: Relevance
“…However, to our knowledge, there is no report to establish the phenotypic changes associated with LdTopII inhibition in this kinetoplastid pathogen. Even in our previous study 4 , we could not identify any remarkable change in parasite morphology by bright field microscopy. The present study establishes that how does the parasite morphology get altered when topoisomerase II is targeted.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…However, to our knowledge, there is no report to establish the phenotypic changes associated with LdTopII inhibition in this kinetoplastid pathogen. Even in our previous study 4 , we could not identify any remarkable change in parasite morphology by bright field microscopy. The present study establishes that how does the parasite morphology get altered when topoisomerase II is targeted.…”
Section: Discussioncontrasting
confidence: 85%
“…Though we proposed earlier an apoptosis-like death mechanism in L . donovani by JVPH3 4 , we were curious to further investigate the subcellular events occurring within the parasite. So, we performed transmission electron microscopy (TEM) to understand the alterations occurring at cell organelles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, reports in the literature have indicated that anti-cancer drugs that affect cellular proliferation can be used as anti-microbial agents because both cell types share common behaviors concerning their high proliferative capabilities [27][28][29]. Indeed, a recent work evidenced the antileishmanial actions of other two isobenzofuranone derivatives and indicated that these actions were due to the induction of reactive oxygen species (ROS)-mediated apoptosis-like cell death and the inhibition of topoisomerases [30].…”
Section: Resultsmentioning
confidence: 99%